EFFECT OF SOY FLOUR INTAKE ON SERUM LIPID PROFILE IN POST MENOPAUSAL WOMEN - DEVIGA.T. M.Sc(N),; PROF.DR.N.HEPSIBAH KIRUBAMANI,; DR.M.BALACHANDRARAO NAIDU M.Sc, (International Journal of Pharma and Bio Sciences, 2016)
The present study was undertaken to evaluate the effect of soy flour intake on lipids and lipoprotein in post menopausal women. This was a three group’s pre and post test design including 30 post menopausal women. The women were randomly divided into 3 groups: study group I, study group II, and control Group. The women in study group I received soy flour 25 gm/day, study group II received soy flour 45gm/day and control group received wheat flour 52g/day, in the form of dosa for the period of 12 weeks. Fasting blood sample were analyzed for serum LDL cholesterol, HDL cholesterol, Triglycerides (TG), Total Cholesterol, Apo lipoprotein A1, Luteinizing hormone (LH), Follicle stimulating hormone (FSH) at the beginning therapy and 12 weeks after initiation of therapy. Soy flour consumption significantly improved LDL, HDL, TG, LH and FSH, but did not have any significant effect on Total cholesterol and Apo lipoprotein A1. In the women taking soy flour 45 gm, it showed a highly significant improvement in lipid profile as compared to study group I and control group. The study reveals that soy flour intake is beneficial for improving lipid profile of post menopausal women.